Do Individuals with and without Autism Spectrum Disorder Scan Faces Differently? A New Multi‐Method Look at an Existing Controversy. Issue 1 (3rd October 2013) - Yi, Li; Feng, Cong; Quinn, Paul C.; Ding, Haiyan; Li, Jiao; Liu, Yubing; Lee, Kang
<x xml:space="preserve">Abstract</x> Individuals with autism spectrum disorder (ASD) are known to process faces atypically. However, there has been considerable controversy regarding whether ASD individuals also scan faces differently from typical adults. Here we compared ASD individuals' face‐scanning patterns with those of typically developing (TD) controls and intellectually disabled (ID) but non‐ASD individuals with the use of an eye tracker and multiple approaches to analyze eye‐tracking data. First, we analyzed the eye movement data with a traditional approach, measuring fixation duration on each area of interest within the face. We found that compared with TD and ID individuals, ASD individuals looked significantly shorter at the right eye. Second, we used a data‐driven method that analyzes fixations on each pixel of the face stimulus and found that individuals with ASD looked more at the central nasal area than TD and ID individuals. Third, we used a novel saccade path analysis that measures frequencies of saccades between major face areas. We found that ASD individuals scanned less often between core facial features than TD individuals but did not differ from ID individuals. Findings from the multi‐method approaches show that individuals with ASD appear not to have a pervasive ASD‐specific atypicality in visual attention toward the face. The ASD‐specific atypical face‐scanning patterns were shown to be limited to fixations on the eyes and nose. Autism Res 2014, 7: 72–83. © 2013 International Society for Autism Research, Wiley Periodicals, Inc.